Work Life Balance: An Overview - Dr. Surbhi Mehra (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Multiple roles performed by individuals call for better integration between work and non-work issues. Even Jobs are no more cushy/easy going, they are demanding. Similarly individual cannot be effective at work if they are not able to manage their personal lives. Finding time for socialization is no more a social obligation, but also a real stress buster. Hence, it has been found that work life balance is not only the source of concern, but also that it is the major source of dissatisfaction for employees. The problem of work life balance is clearly linked with withdrawal behaviour, including employee turnover and some sort of indiscipline or absenteeism.